Ilyas Arabi's Risale-yi Istanbul :|perceptions of architecture and legend through a sixteenth-century Ottoman text - Yıldız, Turhan Ozan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study investigates the perception of Istanbul’s legendary past and Hagia Sophia by early modern Ottoman authors. In doing so, the main source of this study is a mid- 16th century text that is about the legends of Istanbul and the construction narrative of Hagia Sophia and written by Ali el-Arabi Ilyas. In particular, the construction narrative of Hagia Sophia has a long literary history that goes back all the way to the Byzantine era. Therefore, the purpose of this study is two-fold; the first is to diagnose certain connections of these early modern Ottoman texts with Byzantine literary traditions and medieval Islamic traditions. And secondly, by focusing on Ilyas Arabi’s work, it tries to unearth the textual and conceptual convergences and divergences from within the early modern Ottoman text. Since, this study focuses on Ilyas Arabi’s text, it will also pay specific attention of the historical context in which Ilyas wrote this work. Finally, it endeavours to assert and prove the development of a specific pattern of thought pertaining to Constantinopolitan legends and Hagia Sophian narrative by early modern Ottoman authors.